Interplay between the composition of LLDPE/PS blends and their compatibilization with polyethylene-graft-polystyrene in the foaming behaviour1. Issue 34 (15th April 2015) - Zhang, Guangchun; Wang, Yuanliang; Xing, Haiping; Qiu, Jian; Gong, Jiang; Yao, Kun; Tan, Haiying; Jiang, Zhiwei; Tang, Tao
<x xml:space="preserve">Abstract</x> The influences of PE-g-PS compatibilization on the foaming behaviour of LLDPE/PS blends in batch foaming using scCO2 as physical foaming agent depend strongly on the composition of the blends.